The Impact of Emotional Intimacy and Anxiety Sensitivity on Social Functioning: A Cross-Sectional Study - Mata, Giselle; Rodrigues da Silva , Diana; Peixoto , Beatriz (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the predictive relationships between emotional intimacy, anxiety sensitivity, and social functioning in adults. Methods and Materials: A cross-sectional design was employed, with a sample of 318 adults recruited through convenience sampling. Participants completed the Social Functioning Questionnaire (SFQ), Emotional Intimacy Scale (EIS), and Anxiety Sensitivity Index-3 (ASI-3). Descriptive statistics, Pearson correlation analyses, and multiple linear regression were conducted using SPSS version 27 to examine the relationships between the variables. Findings: Pearson correlation analysis revealed a significant positive correlation between emotional intimacy and social functioning (r = 0.57, p < 0.001) and a significant negative correlation between anxiety sensitivity and social functioning (r = -0.46, p < 0.001). The multiple linear regression analysis showed that emotional intimacy and anxiety sensitivity together explained 42% of the variance in social functioning (R² = 0.42, F(2, 315) = 114.28, p < 0.001), with both variables being significant predictors. Conclusion: The study’s findings underscore the importance of emotional intimacy and anxiety sensitivity in influencing social functioning. Higher emotional intimacy enhances social functioning, while higher anxiety sensitivity impairs it.